A world of post politics in Conrad’s the secret agent - Taheri, Zahra (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Joseph Conrad’s The Secret Agent has been hailed as one of the most political works written by the author on terrorism and social upheavals. And it has been a subject of study for many critics. The spectacular feature of his work is described to be in its writer’s imagination to portray the upcoming events related to both world wars, especially the second one and the emergence of Nazi regime and Fascism. However, this article discusses how The Secret Agent, with its shady atmosphere, its projection of runaway consumerism, its display of ‘the passion for the Real,’ its focus on democracy, individual liberty, Capitalism, and the consequences which follow, such as Globalism and imperialism, is much more ahead of its time and delivers the reader a glimpse of what Žižek describes as a ‘Post-political’ era. Through The Secret Agent, the reader is presented with the ‘underbelly,’ as Žižek terms it, of political affairs, and how democracy is a faulty notion just bandied about by the Western societies to preserve their privileges over the ‘Other’. Taking Democracy at face value is, Žižek believes, the first wrong step to approach the era of Post-politics, because it is nothing more than a deliberate evasion of looking into the underside of the current political affairs and describing them exclusively, as Huntington did, as a “clash between civilizations”. It is all but done, Žižek holds, to present the major problems of the world as a clash between Western democracy and Eastern ‘fundamentalist’ in order to keep the distance of ‘us and them’ constant and to conceal the very ‘fundamentalism’ Democracy is stained with in the background of the capitalistic world. It is, however, as Conrad reveals it well, more of a ‘clash within a civilization’ than a ‘clash of the civilizations’—a race for power.